CONSIDERATIONS CONCERNING THE MECHANISM CALLED THE CHEBYSHEV’SăPARADOX - Iulian POPESCU; Liliana LUCA (Fiabilitate şi Durabilitate, 2016)
We study the kinetics of the mechanism called the Chebyshev’s paradox. We show the mechanism consecutive positions, than detailed according to the trigonometrical dials. We notice complex movements, the conducted final part has an irregular movement, with returns. The whole is explained by the appearing of 6 positions where the last conducted part and the anterior crank superpose or prolong each other, the dead point positions where the movements may change the direction. We give the diagrams explaining this ingenuous system.